High-temperature-resistant pressure-sensitive adhesive
By polymerizing acrylate in polysiloxane to form an interpenetrating polymer network structure and adding silicone modified nanoalumina, the existing acrylate pressure-sensitive adhesives have solved the problems of poor thermal conductivity, insufficient insulation performance and poor creep resistance at high temperatures, achieving better high temperature resistance, insulation and creep resistance, and meeting the high-temperature heat dissipation and safety requirements of fast charging technology.
Patent Information
- Application Number
- CN202510428249.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-08
- Publication Date
- 2025-06-17
AI Technical Summary
The existing acrylate pressure-sensitive adhesives have poor thermal conductivity, insufficient insulation performance, and poor creep resistance at high temperatures, making it difficult to meet the high-temperature heat dissipation, insulation and safety requirements of battery adhesives in fast charging technology.
The interpenetrating polymer network structure is formed by acrylate polymerization in polysiloxane and the addition of silicone modified nanoalumina is improved to improve the high temperature, insulation and creep resistance of the colloid.
It significantly improves the high-temperature resistance, insulation and creep resistance of the colloid, enhances its thermal conductivity and safety at high temperatures, and meets the high requirements for battery glue in fast charging technology.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives, and particularly to a high-temperature resistant pressure-sensitive adhesive. Background Art
[0002] With the development of technology, fast charging technology is adopted in more and more fields such as mobile phones and automobiles. However, fast charging is often accompanied by an increase in temperature and an increase in the risk of electric leakage. This puts higher requirements on the performance of battery adhesives. The battery tape is required to provide good thermal conductivity to help dissipate heat, and more importantly, it needs to have properties such as high temperature resistance, insulation, low creep, and shock absorption to improve safety.
[0003] In this case, acrylate pressure-sensitive adhesives are widely used due to their excellent processing performance, excellent long-term use performance, and aging resistance.
[0004] For example, a Chinese patent with the publication number CN109337619B relates to a creep-resistant battery pressure-sensitive adhesive, which includes 10-80 parts of 2-ethylhexyl acrylate, 1-8 parts of 4-methacryloyloxyethyl trimellitic anhydride, 1-20 parts of butyl acrylate, 1-10 parts of methyl methacrylate, 1-10 parts of tetrahydrofurfuryl acrylate, 0.001-1 part of a free radical initiator azobisisobutyronitrile, 0.001-1 part of copper chloride, 0.01-2 parts of pentamethyldiethylenetriamine, 50-250 parts of an organic solvent, 0.1-2 parts of a polyfunctional epoxy resin, 0.01-0.5 part of a curing accelerator, and 1-30 parts of a dye.
[0005] However, including the pressure-sensitive adhesives disclosed in the above patents, the existing acrylate pressure-sensitive adhesives have poor thermal conductivity and cannot dissipate heat in time; they do not have good insulation performance and there is a risk of electric leakage; and at higher application temperatures, the acrylate adhesives have insufficient creep resistance.
[0006] To solve the above problems, the present invention provides a high-temperature resistant pressure-sensitive adhesive. Summary of the Invention
[0007] The purpose of the present invention is to provide a high-temperature resistant pressure-sensitive adhesive to solve the problems raised in the above background art.
[0008] To solve the above technical problems, the present invention provides the following technical solutions:
[0009] A high-temperature resistant pressure-sensitive adhesive, comprising the following substances in parts by weight:
[0010] 50-70 parts of polysiloxane-modified polyacrylate, 2-5 parts of organosilicon-modified nano-aluminum oxide, 5-15 parts of tackifying resin, 0.03-0.3 part of curing agent, 20-50 parts of solvent;
[0011] Among them, the polysiloxane-modified polyacrylate is obtained by polymerizing polyacrylate in a polysiloxane solution, forming an interpenetrating polymer network structure of polysiloxane and polyacrylate.
[0012] Preferably, the synthesis of the polysiloxane-modified polyacrylate comprises the following steps:
[0013] Dissolve 5-20 parts of alkoxysiloxane in 50-80 parts of solvent, add 30-50 parts of acrylate monomer and 2-5 parts of functional monomer after stirring and dissolving, heat up to 65°C, add an initiator accounting for 2-5‰ of the monomer weight and react for 3 hours, then add a supplementary initiator accounting for 1-3‰ and continue reacting for two hours to obtain the polysiloxane-modified polyacrylate.
[0014] Preferably, the alkoxysiloxane is methoxysiloxane or ethoxysiloxane or poly(dimethylsiloxane) capped with alkoxy, and the viscosity at room temperature is 1000-20000 cps.
[0015] Preferably, the viscosity of the alkoxysiloxane at room temperature is 1500-10000 cps.
[0016] Preferably, the acrylate monomer contains at least one (meth)acrylate alkyl ester monomer; among them, the alkyl carbon atom content is 1-12; the (meth)acrylate monomer is at least one of butyl (meth)acrylate, isooctyl acrylate, n-octyl acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, propyl (meth)acrylate, pentyl (meth)acrylate, and isononyl (meth)acrylate.
[0017] Preferably, the theoretical glass transition temperature of the polyacrylate is -60°C to -20°C.
[0018] Preferably, the functional monomer includes acrylate monomers containing at least one crosslinkable group;
[0019] The crosslinkable group contains hydroxyl, carboxyl, that is, it includes at least one of 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, (meth)acrylic acid, maleic acid, oleic acid or itaconic acid.
[0020] Preferably, the functional monomer includes (meth)styrene, benzyl (meth)acrylate, isobornyl (meth)acrylate, vinyl acetate, glycidyl acrylate, (meth)acrylamide or acrylonitrile.
[0021] Preferably, the solvent is at least one of ethyl acetate, methyl acetate, butyl acetate, ethylene glycol methyl ether, propylene glycol methyl ether, toluene, xylene, etc.
[0022] Preferably, the synthesis of organosilicon-modified nano-aluminum oxide comprises the following steps: dispersing nano-aluminum oxide evenly with isopropanol at a mass concentration of 5%-15%, adding a silane coupling agent, acetic acid, and water, stirring at 50-60°C for 4-6 h, and centrifuging after cooling;
[0023] Then washing three times with absolute ethanol to obtain organosilicon-modified nano-aluminum oxide;
[0024] The silane coupling agent is at least one of methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, and ethyltriethoxysilane.
[0025] Preferably, the tackifying resin is at least one of rosin, modified rosin, and terpene phenolic tackifying resin.
[0026] Preferably, the curing agent is at least one of isocyanate curing agents, epoxy curing agents, and aziridine curing agents; or is a curing agent containing metal chelates, including isocyanate curing agents and epoxy curing agents;
[0027] The isocyanate curing agent is at least one of isocyanate curing agents such as toluene diisocyanate, diphenylmethane diisocyanate, tetramethylxylene diisocyanate, hexamethylene diisocyanate, and their trimers;
[0028] The epoxy curing agent is at least one of diglycidyl phthalate, ethylene glycol diglycidyl ether, triglycidyl ether, glycerol diglycidyl ether, and bisphenol A diglycidyl ether.
[0029] Compared with the prior art, the beneficial effects achieved by the present invention are as follows:
[0030] (1) In the present invention, acrylate polymerization is carried out in polysiloxane to form an IPN structure. This structure not only has a damping effect and good shock absorption effect, but can also improve the creep of acrylate. At the same time, the addition of organosilicon also improves the heat resistance and insulation performance of acrylate. After the nano-aluminum oxide is modified with organosilicon, its compatibility with polysiloxane can be improved, which is beneficial to the dispersion of nano-aluminum oxide. The addition of nano-aluminum oxide can further improve its insulation performance and high-temperature resistance.
[0031] (2) In the present invention, polyacrylate polymerization is carried out in a polysiloxane solution to obtain an interpenetrating polymer network structure of polysiloxane and polyacrylate. The formation of this structure can greatly improve the mechanical properties of the polymer system such as creep and impact resistance. The addition of polysiloxane can also improve the high-temperature resistance and insulation performance of the system; the surface modification is carried out by reacting a silane coupling agent with nano-aluminum oxide to increase the dispersion ability of nano-aluminum oxide in the system, while improving the high-temperature resistance and insulation ability of the system. It can also be used as a cross-linking agent for the organosilicon system to form a polymer interpenetrating structure.
[0032] (3) In the present invention, when the acrylate monomer used is a (meth)acrylate monomer with 1-3 alkyl carbon atoms, its homopolymer has a high glass transition temperature and is a high-Tg monomer, which can improve the cohesive force of the polymer; the homopolymer of the (meth)acrylate monomer with 4-12 alkyl carbon atoms has a low glass transition temperature and is a low-Tg monomer, which can improve the adhesive ability of the polymer. By adjusting the ratio of the acrylate monomers, the glass transition temperature of the polyacrylate can be adjusted.
[0033] (4) In the present invention, after being modified by a silane coupling agent, nano-aluminum oxide not only has improved dispersion ability in the system, but also can react with alkoxy polysiloxane after being blended with polysiloxane-modified polyacrylate to act as a crosslinking point of the polysiloxane phase and form an interpenetrating network structure.
[0034] (5) In the present invention, polysiloxane has good heat-resistant insulation performance. As a filler, nano-aluminum oxide can not only reinforce the acrylate adhesive, but also improve its high-temperature insulation performance and endow the silicone with thermal conductivity. Specific embodiments
[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of them. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0036] In the present invention, by using the polymerization of polyacrylate in polysiloxane to form an IPN structure, the compatibility between polyacrylate and polysiloxane is improved, the high-temperature resistance of the colloid is improved, and organosilicon-modified nano-aluminum oxide crosslinking is added to the formula. The pressure-sensitive adhesive is mainly completed through the following steps:
[0037] Synthesis example
[0038] Prepare organosilicon-modified nano-aluminum oxide. Dilute 20 parts of nano-aluminum oxide with isopropanol at a mass concentration of 10% and disperse it evenly. Add 2 parts of silane coupling agent methyltrimethoxysilane, 0.05 part of acetic acid, and 0.8 part of water to the solution, stir at 60 °C for 5 h, centrifuge after cooling, and wash three times with absolute ethanol to obtain organosilicon-modified nano-aluminum oxide.
[0039] Synthesis example 1
[0040] Preparation of polysiloxane-modified polyacrylate. 5 parts of methoxy polydimethylsiloxane was dissolved in 50 parts of ethyl acetate by stirring, and then 25 parts of butyl acrylate, 5 parts of methyl acrylate, and 2 parts of hydroxybutyl acrylate were added. After stirring evenly, the temperature was raised to 65 °C under nitrogen. After the temperature was stabilized, 0.07 part of azobisisobutyronitrile was added. After reacting for 3 h, 0.04 part of the initiator azobisisobutyronitrile was added, and the reaction continued for 3 h and then ended. After cooling to room temperature, polysiloxane-modified polyacrylate Synthesis Example 1 was obtained.
[0041] Synthesis Example 2
[0042] Preparation of polysiloxane-modified polyacrylate. 10 parts of methoxy polydimethylsiloxane was dissolved in 80 parts of ethyl acetate by stirring, and then 10 parts of isooctyl acrylate, 35 parts of butyl acrylate, 10 parts of methyl acrylate, and 3 parts of acrylic acid were added. After stirring evenly, the temperature was raised to 65 °C under nitrogen. After the temperature was stabilized, 0.15 part of azobisisobutyronitrile was added. After reacting for 3 h, 0.1 part of the initiator azobisisobutyronitrile was added, and the reaction continued for 3 h and then ended. After cooling to room temperature, polysiloxane-modified polyacrylate Synthesis Example 1 was obtained.
[0043] Synthesis Example 3
[0044] Preparation of polysiloxane-modified polyacrylate. 20 parts of methoxy polydimethylsiloxane was dissolved in 80 parts of ethyl acetate by stirring, and then 50 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, and 2 parts of acrylic acid were added. After stirring evenly, the temperature was raised to 65 °C under nitrogen. After the temperature was stabilized, 0.3 part of azobisisobutyronitrile was added. After reacting for 3 h, 0.1 part of the initiator azobisisobutyronitrile was added, and the reaction continued for 2 h and then ended. After cooling to room temperature, polysiloxane-modified polyacrylate Synthesis Example 3 was obtained.
[0045] Synthesis of polyacrylate
[0046] 25 parts of butyl acrylate, 5 parts of methyl acrylate, and 2 parts of hydroxybutyl acrylate were added to 50 parts of ethyl acetate by stirring. After stirring evenly, the temperature was raised to 65 °C under nitrogen. After the temperature was stabilized, 0.07 part of azobisisobutyronitrile was added. After reacting for 3 h, 0.04 part of the initiator azobisisobutyronitrile was added, and the reaction continued for 3 h and then ended. After cooling to room temperature, polyacrylate was obtained.
[0047] In the present invention, high-temperature resistant pressure-sensitive adhesives were prepared through several examples and comparative examples, and their respective performances were verified by comparison. The specific formulations in each example and comparative example are shown in Table 1.
[0048] Table 1 Formulation table of each example and comparative example
[0049]
[0050]
[0051] After stirring the above formulations of each example and comparative example evenly, apply the glue on the release film and dry it. The dry glue thickness is 300 μm. After curing the glue film for 3D, conduct tests. The test results are shown in Table 2. The specific test methods include:
[0052] 1. (High temperature) Bonding effect test:
[0053] Test the bonding effect of the glue film by measuring the peel strength between the glue film and the SUS steel plate. The peel strength test is carried out with reference to the standard "Test Method for Peel Strength of Adhesive Tapes" (GB / T 2792-2014). The high-temperature bonding effect is tested by the peel strength at 85°C. The test method is that the above glue film is sampled on the substrate according to the standard of "Test Method for Peel Strength of Adhesive Tapes" (GB / T 2792-2014) and then placed in an 85°C constant temperature for 24 h and directly tested;
[0054] 2. Creep resistance test
[0055] Stack the glue films of each example and comparative example into a glue film with a thickness of about 1000 μm, cut it into samples with a diameter of 25 mm, and use a rotational rheometer to conduct creep recovery tests. The test temperature is 25°C, the stress is 10000 Pa, the stress is applied for 300 s and then the stress is removed and the recovery is for 600 s. Record the creep recovery rate after 600 s;
[0056] 3. High-temperature holding force test
[0057] Measure according to the method of GB / T 4851-2014. Stick the standard tape (width 25 mm, length 100 mm) on the stainless steel plate, align the upper end with the standard line, cut off the excess part at the lower end, roll it back and forth 3 times with a 2 kg pressure roller, and after placing it for 48 h, hang the stainless steel plate with the sample vertically on the test rack without allowing it to shake, hang a 1 kg weight below, hang the sample in an 85°C oven for 72 h, and use the downward displacement of the tape to represent the holding force of the pressure-sensitive adhesive. If the weight drops, it is NG.
[0058] 4. Insulation performance test
[0059] Conduct volume resistance tests on the glue film according to GB / T 1410-2006, at a voltage of 1000 V. The electrodes are metal strip clips with dimensions of 10 (±0.5) mm * 10 (±0.5) mm * 50 ± 0.5 mm, and the distance between the two electrodes is 25 ± 0.5 mm. Record the ratio of voltage to current as the insulation resistance after the current is stable.
[0060] The insulation performance at high temperature is to conduct the above insulation test after keeping the sample at 80°C for 24 h.
[0061] 5. Drop hammer impact test
[0062] The impact resistance of the examples and comparative examples was measured according to ASTM D5628. Using a pressure-sensitive adhesive in the shape of a figure-eight (outer frame 24.5 mm, inner frame 20.5 mm, 2.0 mm width), SUS stainless steel (24.5 mm * 24.5 mm * 3 mm) was bonded to a 3-mm figure-eight SUS stainless steel (outer frame 40 mm, inner frame 20 mm) to obtain the sample to be tested. Then, a 6.2-kg weight was placed on top of the sample for 10 seconds, and the sample was left at room temperature for 48 h before testing. The testing equipment was Instron CEAST9340. The sample was impacted by dropping a 3.00-kg (standard crossbeam + weight) from a height of 100 cm, and the total impact energy (total energy) required to release the bond of the SUS stainless steel substrate was measured and recorded. 2 Using a pressure-sensitive adhesive in the shape of a figure-eight (outer frame 24.5 mm, inner frame 20.5 mm, 2.0 mm width), SUS stainless steel (24.5 mm * 24.5 mm * 3 mm) was bonded to a 3-mm figure-eight SUS stainless steel (outer frame 40 mm, inner frame 20 mm) to obtain the sample to be tested. Then, a 6.2-kg weight was placed on top of the sample for 10 seconds, and the sample was left at room temperature for 48 h before testing. The testing equipment was Instron CEAST9340. The sample was impacted by dropping a 3.00-kg (standard crossbeam + weight) from a height of 100 cm, and the total impact energy (total energy) required to release the bond of the SUS stainless steel substrate was measured and recorded.
[0063] Table 2 Test results of each example and comparative example
[0064]
[0065]
[0066] Combining Table 1 and Table 2, it can be seen that in the present invention, by carrying out the polymerization of polyacrylate in polysiloxane to form an IPN structure, the compatibility between polyacrylate and polysiloxane is improved, the high-temperature resistance of the colloid is improved, and organosilicon-modified nano-aluminum oxide is added to crosslink polysiloxane in the formulation, and a curing agent is added to crosslink polyacrylate to form a polymer interpenetrating network structure, thereby improving the creep resistance and impact resistance of the whole system. At the same time, both polysiloxane and nano-aluminum oxide have good high-temperature resistance and insulation properties, and the addition of the two endows the system with excellent high-temperature bonding properties and insulation properties.
[0067] In Comparative Examples 1 and 3, organosilicon-modified nano-aluminum oxide was not added, and the polysiloxane in the system could not crosslink to form a stable IPN structure, resulting in a decrease in the creep recovery of the system, phase separation at high temperature, which affected the peel strength and also affected the high-temperature holding force. In Comparative Example 1, nano-aluminum oxide was not contained, resulting in a decrease in the insulation performance of the system. In Comparative Example 2, a tackifying resin was not added, resulting in a decrease in the peel strength of the system. In Comparative Example 4, only polyacrylate was used, and the addition of polysiloxane was not added, resulting in a decrease in both the high-temperature and insulation properties of the system, and the system could not form an IPN structure, resulting in a decrease in creep recovery.
[0068] In Comparative Example 5, although polysiloxane was added, simple blending limited the dispersion effect of polysiloxane in acrylate, and phase separation was easy to occur. Organosilicon-modified nano-aluminum oxide was more easily dispersed in polysiloxane, and crosslinking polysiloxane further aggravated phase separation, seriously affecting the mechanical properties of the system, and the peel strength and creep were significantly reduced.
[0069] The above are only alternative embodiments of the present invention, and do not limit the patent scope of the present invention accordingly. Any equivalent structure or equivalent process transformation made by using the content of the specification of the present invention under the inventive concept of the present invention, or directly or indirectly applied to other related technical fields, shall be similarly included in the patent protection scope of the present invention.
Claims
1. A high temperature resistant pressure sensitive adhesive, characterized in that: The following materials are included in weight: 50-70 parts of polysiloxane modified polyacrylate, 2-5 parts of organosilicon modified nano-alumina, 5-15 parts of tackifying resin, 0.03-0.3 parts of curing agent, 20-50 parts of solvent; The polysiloxane-modified polyacrylate is obtained by polymerizing acrylate in a polysiloxane solution to form an interpenetrating polymer network structure of polysiloxane and polyacrylate.
2. A high temperature resistant pressure sensitive adhesive according to claim 1, characterized in that: The synthesis of the polysiloxane-modified polyacrylate comprises the following steps: Dissolve 5-20 parts of alkoxy polysiloxane in 50-80 parts of solvent, stir and dissolve, add 30-50 parts of acrylate monomer and 2-5 parts of functional monomer, heat to 65°C, add 2-5‰ of initiator by weight of monomer and react for 3 hours, then add 1-3‰ of initiator and continue to react for two hours to obtain polysiloxane modified polyacrylate.
3. The high temperature resistant pressure sensitive adhesive according to claim 2, characterized in that: The alkoxy polysiloxane is a methoxy or ethoxy or alkoxy terminated polydimethylsiloxane, and has a viscosity of 1000-20000 cps at room temperature.
4. The high temperature resistant pressure sensitive adhesive according to claim 3, characterized in that: The room temperature viscosity of the alkoxy polysiloxane is 1500-10000 cps.
5. The high temperature resistant pressure sensitive adhesive according to claim 2, characterized in that: The acrylic acid ester monomer comprises at least one (meth) acrylic acid alkyl ester monomer, wherein the alkyl carbon atom content is 1-12; the (meth) acrylic acid ester monomer is at least one of butyl (meth) acrylate, isooctyl acrylate, n-octyl acrylate, ethyl (meth) acrylate, methyl (meth) acrylate, propyl (meth) acrylate, pentyl (meth) acrylate, and isononyl (meth) acrylate.
6. The high temperature resistant pressure sensitive adhesive according to claim 5, characterized in that: The theoretical glass transition temperature of the polyacrylate is -60°C to -20°C.
7. The high temperature resistant pressure sensitive adhesive according to claim 2, characterized in that: The functional monomer includes an acrylate monomer containing at least one cross-linkable group; The crosslinkable group comprises a hydroxyl group, a carboxyl group, namely, hydroxyethyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxypropyl (meth)acrylate, (meth)acrylic acid, maleic acid, oleic acid or itaconic acid.
8. The high temperature resistant pressure sensitive adhesive according to claim 2, characterized in that: The functional monomers include (methyl)styrene, benzyl (methyl)acrylate, isobornyl (methyl)acrylate, vinyl acetate, glycidyl acrylate, (methyl)acrylamide or acrylonitrile.
9. The high temperature resistant pressure sensitive adhesive according to claim 2, characterized in that: The solvent is at least one of ethyl acetate, methyl acetate, butyl acetate, ethylene glycol methyl ether, propylene glycol methyl ether, toluene, xylene and the like.
10. The high temperature resistant pressure sensitive adhesive according to claim 1, characterized in that: The synthesis of the organosilicon-modified nano-alumina comprises the following steps: dispersing the nano-alumina uniformly with isopropanol at a mass concentration of 5%-15%, adding a silane coupling agent, acetic acid and water, stirring at 50-60° C. for 4-6 hours, cooling and centrifuging; Then washing with anhydrous ethanol three times to obtain organosilicon-modified nano-alumina; The silane coupling agent is at least one of methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane and ethyltriethoxysilane.
11. The high temperature resistant pressure sensitive adhesive according to claim 1, characterized in that: The tackifying resin is at least one of rosin, modified rosin and terpene phenol tackifying resin.
12. The high temperature resistant pressure sensitive adhesive according to claim 1, characterized in that: The curing agent is at least one of an isocyanate curing agent, an epoxy curing agent, and an aziridine curing agent; or a curing agent containing a metal chelate, including an isocyanate curing agent and an epoxy curing agent; The isocyanate curing agent is at least one of isocyanate curing agents such as toluene diisocyanate, diphenylmethane diisocyanate, tetramethylxylene diisocyanate, hexamethylene diisocyanate and trimers thereof; The epoxy curing agent is at least one of diglycidyl phthalate, ethylene glycol diglycidyl ether, triglycidyl ether, glycerol diglycidyl ether, and bisphenol A diglycidyl ether.
Citation Information
Patent Citations
Anti-creep battery pressure-sensitive adhesive and its preparation method, and battery insulating protective blue film
CN109337619B
Silane modified polyacrylate sealant and preparation method thereof
CN112538326A
Polyacrylate / organic silicon hybrid pressure-sensitive adhesive
CN114989731A
Organosilicon modified acrylate binder and preparation method thereof
CN116731648A
High-temperature-resistant polyacrylate / organic silicon hybrid pressure-sensitive adhesive and preparation method thereof
CN116855205A